Hak Regres PT PII terhadap Penanggung Jawab Proyek Kerjasama dalam Mekanisme Kerjasama Pemerintah dan Badan Usaha - Riyadh Raihan Dhawy Fayiz; Fadly Madani; Ary Syafei Ar Rashid (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The Public-Private Partnership (PPP) scheme with guarantees from PT PII aims to accelerate infrastructure development through private participation, but faces legal and practical challenges, particularly related to the risk of default by the Government and Construction Service Provider (GCA) and the effectiveness of the implementation of recourse rights by PT PII towards government institutions. This study uses a normative juridical method with an analytical descriptive approach through a literature study of primary and secondary legal materials, as well as a qualitative analysis of legal documents, to understand in depth the application of recourse rights to GCA in the PPP mechanism. The application of recourse rights by PT PII as a PPP project guarantor is based on a special legal framework and complex contractual agreements to protect investors from the risk of default by the GCA. However, its implementation has the potential to face legal, political, bureaucratic, and fiscal challenges that can affect the effectiveness of protection and the fiscal sustainability of PT PII. PT PII's recourse rights in the PPP scheme are an adaptation of the borgtocht concept applied lex specialis through the PPP agreement, guarantees, and recourse to protect state finances. However, its implementation faces bureaucratic, budgetary, and fiscal constraints that can hamper its effectiveness. Therefore, binding guidelines and increased institutional capacity are needed to ensure that regress rights can be exercised effectively, accountably, and in accordance with the principles of transparency and accountability. This study concludes that to increase the effectiveness of the PPP scheme, improvements in the legal framework, inter-agency coordination, and strengthening the capacity of institutions involved in implementing regress rights are needed.